The Man Who ''Invented'' the Aztec Crystal Skulls : the Adventures of Eugène Boban. - Walsh, Jane MacLaren (Berghahn Books, Incorporated, 2018)
EugEne Boban began life in humble circumstances in Paris, traveled to the California Gold Rush, and later became a recognized authority on pre-Columbian cultures.' He also invented an entire category of archaeological artifact: the Aztec crystal skull. By his own admission, he successfully 'palmed off' a number of these crystal skulls on the curators of Europe's leading museums. How could that happen, and who was this man' Detailed are the travels, self-education, and archaeological explorations of EugEne Boban; this book also explores the circumstances that allowed him to sell fakes to museums that would remain undetected for over a century.